A CRITICAL REVIEW OF RECENT INVESTIGATIONS ON TWO-PHASE PRESSURE DROP IN FLOW BOILING MICRO-CHANNELS - Somchai Wongwises; Sira Saisorn (My University, 2012)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Thermal fluids; Frontier; Flow boiling; Heat Transfer and Boiling Studies